Determination of some Quality Characteristics in Chickpea (Cicer arietinum L.) Genotypes and Relationships between Characteristics - Sinem Tuğçe Cin; Nurdoğan Topal (Turkish Journal of Agriculture: Food Science and Technology)
Chickpea (Cicer arietinum L.) is one of the important plants in terms of nutrition. The yield and quality studies on chickpea, which has the highest production value among edible grain legumes, continue at full stem in our country. When it comes to quality, certain consumer expectations such as protein content, cooking time and seed coat ratio dominate the quality improvement. This study was conducted according to the experimental designs of randomized blocks under the Faculty of Agriculture and Natural Sciences, Uşak University and the laboratory conditions of Faculty of Agriculture, Ondokuz Mayıs University. In this study, a total of 30 chickpea genotypes were used, 13 of them have different varieties. Cooking Time (min), Water Absorption Index (%), Seed Coat Rate (%), Protein Rate (%) and Amylose Rate (%) values of the genotypes have been obtained. The statistically significant differences have been detected between the genotypes in terms of all parameters examined in the variance analysis conducted as a result of this study. Similarly, the result of this study has revealed the correlation between the properties. This study was obtained from a part of the master’s thesis.